ASSISTANCE FOR MICRO SMALL, AND MEDIUM ENTERPRISES THROUGH LEARNING HOW TO MAKE FINANCIAL REPORTS AND TAX AWARENESS IN MADIDIR WERU VILLAGE - Evinita, Lenny Leorina; Pandowo, Adithya; Purba, Pebisitona; Paoki, Rouna (LPPM Univ. Ibn Khaldun Bogor, 2023)
The purpose of this activity is to provide progress for Micro Small Medium Enterprises actors in proper financial planning and management to improve the income and increase knowledge about taxes. It is found many beginner MSME business people who doesn’t understand how to manage finances. Based on the phenomenon of the problems that occurs and the result of discussion with partners, The method used to improve the performance of MSME actors can carry out proper management of finances by gave training activities how to provide simple financial report and give a knowledge about taxes so the MSME actors in Madidir Weru can compete with the business world.